Valores elevados de oximetría de pulso como factor de riesgo de retinopatía del prematuro en el Hospital Belén de Trujillo - Marreros Aquino, Nicole Mayumy (2018)
The present study was carried out with the objective of determining if the high values of pulse oximetry (> 90%) constitute a risk factor for retinopathy of prematurity (ROP) in neonates of the Neonatology service of the Belén de Trujillo Hospital. For this purpose, a retrospective analytical study of cases and controls was carried out, with a population of 104 neonates with less than 1500 g of birthweight and less than 32 weeks of gestational age registered between the 2012-2017 period; divided into 2 groups: with ROP and without it; the odds ratio and the chi square test were calculated. Obtaining that the averages of gestational age and birth weight were significantly lower in the group with ROP than in the group without ROP. The frequency of high pulse oximetry values in neonates with ROP was 52%, while 25% in those without ROP (p <0.05). It should be noted that there were significant differences between both population samples in terms of gestational age and birth weight, so that the variables in question could be considered confusing, in addition, other possible intervening variables were not considered. Nevertheless; Corroborate that high values of pulse oximetry are a risk factor for ROP